Pushing Cherenkov PET with BGO via coincidence time resolution classification and correction. (2nd June 2020) - Kratochwil, Nicolaus; Gundacker, Stefan; Lecoq, Paul; Auffray, Etiennette
Abstract: Bismuth germanate (BGO) shows good properties for positron emission tomography (PET) applications, but was substituted by the development of faster crystals like lutetium oxyorthosilicate (LSO) for time-of-flight PET (TOF-PET). Recent improvements in silicon photomultipliers (SiPMs) and fast readout electronics make it possible to access the Cherenkov photon signal produced upon 511 keV interaction, which makes BGO a cost-effective candidate for TOF-PET. Tails in the time-delay distribution, however, remain a challenge. These are mainly caused by the high statistical fluctuation on the Cherenkov photons detected. To select fast events with a high detected Cherenkov photon number, the signal rise time of the SiPM was used for discrimination. The charge, time delay and signal rise time was measured for two different lengths of BGO crystals coupled to FBK NUV-HD SiPMs and high frequency readout in a coincidence time resolution setup. The recorded events were divided into 5 × 5 categories based on the signal rise time, and time resolutions of 200 ± 3 ps for 2 × 2 × 20 mm 3 and 117 ± 3 ps for 2 × 2 × 3 mm 3 were measured for the fastest 20% of the events (4% in coincidence). These good timing events can provide additional information for the image reconstruction in order to increase the SNR significantly, without spoiling the detector sensitivity. Putting all photopeak events together and correcting for the time bias introduced by different numbers of Cherenkov photons detected, time resolutions of 259 ± 3 ps for 20 mm long and 151 ± 3 ps for 3 mm long crystals were measured. For a small fraction of events sub-100 ps coincidence time resolution with BGO was reached for a 3 mm short pixel.